A Multiplexed Quantitative Proteomics Approach to the Human Plasma Protein Signature - Estefanía Núñez; María Gómez-Serrano; Enrique Calvo; Elena Bonzon-Kulichenko; Marco Trevisan-Herraz; José Manuel Rodríguez; Fernando García-Marqués; Ricardo Magni; Enrique Lara-Pezzi; José Luis Martín-Ventura; Emilio Camafeita; Jesús Vázquez (Biomedicines)
Despite the plasma proteome being able to provide a unique insight into the health and disease status of individuals, holding singular promise as a source of protein biomarkers that could be pivotal in the context of personalized medicine, only around 100 proteins covering a few human conditions have been approved as biomarkers by the US Food and Drug Administration (FDA) so far. Mass spectrometry (MS) currently has enormous potential for high-throughput analysis in clinical research; however, plasma proteomics remains challenging mainly due to the wide dynamic range of plasma protein abundances and the time-consuming procedures required. We applied a new MS-based multiplexed proteomics workflow to quantitate proteins, encompassing 67 FDA-approved biomarkers, in >1300 human plasma samples from a clinical cohort. Our results indicate that this workflow is suitable for large-scale clinical studies, showing good accuracy and reproducibility (coefficient of variation (CV) < 20 for 90% of the proteins). Furthermore, we identified plasma signature proteins (stable in time on an individual basis), stable proteins (exhibiting low biological variability and high temporal stability), and highly variable proteins (with low temporal stability) that can be used for personalized health monitoring and medicine.